A Novel Approach to Algorithmic Encoding and Decoding by Tribonacci Matrices - Aljalali, Osamah A.; Altirban, Aml A.; Abu Irzayzah, Samyrah M.; El Bolati, Tawfik A. (Iraqi Journal of Science, 2026)
In this paper, we discuss a new, effective technique for encoding and decoding text that uses Tribonacci numbers to boost security and make it harder to figure out the right keys needed for decryption. We focused on developing different algorithms and methods to protect different types of data, especially text messages, and making it very difficult for unauthorized people to access them and be able to break these codes.  Strong data protection is needed for a variety of applications, and the suggested algorithm offers promising results in terms of encryption and decryption accuracy. This paper demonstrates the potential of Tribonacci matrix-based algorithms in advancing the landscape of secure communication protocols.